Suppression of tropomyosin synthesis, a common biochemical feature of oncogenesis by structurally diverse retroviral oncogenes. - Herbert L. Cooper; Nili Feuerstein; Makoto Noda; Robert H. Bassin (1985)
To identify proteins whose production may be altered as a common event in the expression of structurally diverse oncogenes, we compared two-dimensional electropherograms of newly synthesized proteins from NIH/3T3 cell lines transformed by a variety of retroviral oncogenes, from cellular revertant lines, and from a line (433.3) which expresses the v-ras oncogene in response to corticosteroids. Most alterations in the synthesis of specific proteins detected by this approach appeared to be the result of selection during prolonged cultivation and were probably unrelated to the transformation process. However, we detected seven proteins whose synthesis was strongly suppressed in cell lines transformed by each of the six retroviral oncogenes we studied and whose production was fully or partially restored in two cellular revertant lines. Suppression of two of these proteins was also correlated with the initial appearance of morphological alteration during corticosteroid-induced oncogene expression in 433.3 cells. These proteins (p37/4.78 and p41/4.75) were identified as tropomyosins, a group of at least five cytoskeletal proteins. Transformation by the papovaviruses simian virus 40 and polyomavirus caused no suppression of synthesis of these tropomyosins. This indicates that suppression of tropomyosin synthesis is not a nonspecific response by cells to being forced to grow with the transformed phenotype but is specifically associated with oncogenesis by diverse retroviral oncogenes. The results are consistent with the hypothesis that the different biochemical processes initiated by expression of structurally diverse retroviral oncogenes may converge on a limited number of common targets, one of which is the mechanism which regulates the synthesis of tropomyosins.